2018
DOI: 10.1007/s00270-018-1901-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mechanical Thrombectomy Using Stent Retriever and Balloon-Guiding Catheter

Abstract: Even a standard thrombectomy technique with the use of a stent retriever together with a balloon-guiding catheter provides reasonable recanalization rates with only one passage. The results can be taken as benchmark for alternative and more complex techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…15 Additionally, the combination of a stentriever with PBGC has been previously reported as a feasible combinational approach, achieving first-pass recanalization in 110/170 (65%) of patients. 16 Consistent with these findings, we found that the use of PBGC was strongly associated with cFPE (mTICI 2c–3). Our findings support the concept that mTICI 2c and 3 may be a homogeneous group of patients where no (or less) distal emboli were produced during MT.…”
Section: Discussionsupporting
confidence: 88%
“…15 Additionally, the combination of a stentriever with PBGC has been previously reported as a feasible combinational approach, achieving first-pass recanalization in 110/170 (65%) of patients. 16 Consistent with these findings, we found that the use of PBGC was strongly associated with cFPE (mTICI 2c–3). Our findings support the concept that mTICI 2c and 3 may be a homogeneous group of patients where no (or less) distal emboli were produced during MT.…”
Section: Discussionsupporting
confidence: 88%
“…Good clinical outcome at 3 months was higher in younger patients and those with lower NIHSS score at baseline, higher ASPECTS at admission, lower procedure time, fewer number of passes, and higher FPE rate. Good clinical outcome at 3 months was also more common in patients with lower NIHSS score at 24 hours [4 (IQR1-8) vs 16 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)] (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In this setting, previous studies have reported positive correlation between the use of a balloon guide catheter (BGC) and higher successful recanalization rates, shorter procedure times, better clinical outcomes, and lower risk of mortality. [12][13][14][15][16][17][18][19][20][21][22][23][24] As such, the use of BGCs is recommended in stent-retriever thrombectomy in current guidelines. 1 However, despite the preponderance of data in favor of BGC use, many neurointerventionists remain reluctant to use BGC due to different concerns including difficulty in navigating the device, the greater potential for groin complications due to the larger required femoral access, risk of carotid dissection, and compatibility of BGC with larger-bore distal aspiration catheters.…”
Section: Introductionmentioning
confidence: 99%
“…The BGC allows for effective MT with an increased possibility of clot removal and reduced distal emboli, via proximal blood flow arrest and increasing suction effectiveness (9,10,18). The effect of proximal blood flow control in FG2 and Merci is considered to be the same, because they have same 8 F outer diameter and balloon size; however, the incidence rate of distal emboli was significantly lower in the FG2 group compared with the Merci group, and the use of FG2 was revealed to be associated with reduced distal emboli in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%